2011
DOI: 10.5194/angeo-29-2225-2011
|View full text |Cite
|
Sign up to set email alerts
|

Statistical study of the DP2 enhancement at the dayside dip-equator compared to low latitudes

Abstract: Abstract. It has been largely investigated and established that the DP2 events are enhanced at dip-equator compared to low latitudes. Studies by several authors showed various enhancement ratio values of DP2 amplitude at the dayside dipequator relative to those at low latitudes. In order to quantify this enhancement ratio, we carried out a statistical study on this phenomenon using the ground magnetometer data at locations ranging from polar cap to dip-equator over the African, Asian and American sector. Our r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Kashcheyev et al, 2018, have showed the difference in PPEF response as a function of longitude at the beginning of a magnetic storm. Different authors have studied the latitudinal profiles of PPEF in a given longitude sector (Kikuchi et al, 2000; Kobea et al, 2000; Mazaudier et al, 1984; Mene et al, 2011). The diurnal oscillations—having periods between 16 and 28 hr—which can be associated with D dyn are extracted using a band‐pass filter.…”
Section: Discussionmentioning
confidence: 99%
“…Kashcheyev et al, 2018, have showed the difference in PPEF response as a function of longitude at the beginning of a magnetic storm. Different authors have studied the latitudinal profiles of PPEF in a given longitude sector (Kikuchi et al, 2000; Kobea et al, 2000; Mazaudier et al, 1984; Mene et al, 2011). The diurnal oscillations—having periods between 16 and 28 hr—which can be associated with D dyn are extracted using a band‐pass filter.…”
Section: Discussionmentioning
confidence: 99%
“…The periods of DP2 are on average of the order of minutes to 3hours. During the last decades many experimental and theoretical studies highlighted the characteristics of prompt penetration of magnetospheric convection (Fejer et al, 1983;Mazaudier et al, 1984;Spiro et al, 1988;Fejer and Scherliess, 1997;Kobéa et al, 1998Kobéa et al, , 2000Peymirat et al, 2000;Mene et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The magnetic disturbance associated to this physical process was named DP 2 by Nishida [1968]. Many experimental and theoretical studies of the prompt penetration of magnetospheric convection were made during the last decades [ Vasyliunas , 1970; Senior and Blanc , 1984; Mazaudier , 1985; Spiro et al , 1988; Kikuchi et al ,1996; Kobéa et al , 1998, 2000; Peymirat et al 2000; Mene et al , 2011].…”
Section: Introductionmentioning
confidence: 99%